Off-pump or on-pump coronary artery bypass at 30 days: A propensity matched analysis - Wang, Chen; Jiang, Yefan; Song, Yu; Wang, Qingpeng; Tian, Rui; Wang, Dashuai; Dong, Nianguo; Jiang, Xionggang; Chen, Si; Chen, Xinzhong (Frontiers in Cardiovascular Medicine, 2022)
Introduction This study was to determine whether coronary artery bypass grafting without cardiopulmonary bypass (off-pump CABG, OPCAB) could reduce early postoperative mortality and major complications compared with conventional coronary artery bypass grafting with cardiopulmonary bypass (on-pump CABG, ONCAB) by experienced surgeons. Material and methods From January 2016 to June 2020, isolated CABG was performed in 1200 patients (ONCAB 429, OPCAB 771) in Wuhan Union Hospital. The propensity score matching was used to adjust for differences in baseline characteristics between the ONCABG and OPCABG groups. After 1:1 matching, 404 pairs for each group were selected to compare outcomes within 30 days after surgery. All the operations were completed by experienced surgeons that had completed more than 500 on-pump and 200 off-pump CABG, respectively. Results After propensity matching, the two groups were comparable in terms of preoperative characteristics. The OPCAB group had less vein graft (2.5 ± 1.0 vs. 2.7 ± 0.9; P < 0.001) and a higher rate of incomplete revascularization (12.4 vs. 8.2%; P < 0.049) than the ONCAB group. There was no significant difference in early postoperative mortality between ONCAB and OPCAB groups (2.2 vs. 2.2%; P = 1.00). However, patients in the OPCAB group had a lower risk of postoperative stroke (1.5 vs. 4.7%; P = 0.008), new-onset renal insufficiency (8.9 vs. 18.8%; P < 0.001), respiratory failure (2.2 vs. 7.2%; P = 0.001), reoperation for bleeding (0.5 vs. 2.7%; P = 0.001), and required less ventilator assistance time (33.4 ± 37.9 h vs. 51.0 ± 66.1 h; P < 0.001) and intensive care unit (ICU) time (3.7 ± 2.7 days vs. 4.8 ± 4.3 days; P < 0.001). Conclusions In our study, patients undergoing OPCAB had fewer postoperative complications and a faster recovery. It is a feasible and safe surgical approach to achieve revascularization when performed by experienced surgeons.